Teologia inclusiva nas redes sociais: Evangelização inclusiva segundo a Igreja Comunidade Metropolitana em João Pessoa. - Lorenzo, Daniel de Andrade (2016)
The dissertation presents a study on the intention to spread in social networking, institutional advertisements of inspiration to inclusive Christian dogmatic interpretation. The study was produced by participant observation in an evangelical community in developing João Pessoa, and seeks to differentiate highlighting the importance of religious same-sex marriage. Dialogue through inductive and deductive methods hypothetical was first produced a speculative hypothesis, which, exposed to everyday narrative reflections on theories of communication and digital media, elucidated limits and limitations of inclusive evangelism religious content shared on social networking site. In order to understand the community in everyday life, the research was carried out to evaluate hypotheses about the institutional visibility of the movement on the social network in contrast to the increasing public dispersion. We observe the development of ideological bubbles where the spread of inclusive message, searching for new fans to inclusive Christianity in social network Facebook, has mitigated the effects from the proximity of the interpretive algorithms contradictions motivated by simplifying dichotomous arguments. By contrast, one sees the sharing of Christian inspiration contents as an individual expression to testify religious experience in the community and simultaneously spread the representation according to principles than Watts (2013) suggests as Halo and Matthew effects. In this context, scientific research in social communication is presented as a methodological reading clippings fluid processes, inaccurate, and fundamental understanding of the study through dialogues between theories of the Palo Alto School and perceptions of cibercotidiano virtual forum ICM Joao Pessoa on the Facebook social network.